Atomization of liquid and gelled simulant propellants by impinging jets - Gabriel Silva Dias (2020)
This work presents an experimental study of the atomization process by jet impingement of liquid and gelled simulant propellants. Like and unlike jets of liquid water, gelled water, liquid hydrous ethanol and gelled hydrous ethanol were tested for different injection pressures, collision distances and collision angles. Experimental data were given in terms of jet momenta and conventional or generalized non-dimensional numbers, Re, Regen, We and Wegen, for liquids and gels. A power law model was adopted to represent the gelled fluids and to define the generalized parameters. Shadow images of the collision sheets were obtained with help of a high speed camera and droplet velocities were calculated by an open PIV software. A patternator was used to estimate mass flux distributions of the sprays formed. Droplet size distributions and representative droplet diameters (SMD and Dv10) were determined by a laser diffraction system. Collision sheet geometries were compared to theoretical model predictions, showing good agreement for liquids. Experimental spray mass flux distributions presented a good agreement with literature data. Images from a high speed camera showed that gel sprays can form complex structures with presence of holes, rails and/or fishbone geometries. Disturbances and impact waves in the collision sheet produce ligaments from which droplets are detached. Transient behavior was observed in some cases with presence of different geometrical configurations. Long ligaments require larger distances to fragment into drops and even with high injection pressures some ligaments do not break up. Such delay or no ligament disintegration of the gel film probably occurs as consequence of the absence or low intensity of impact waves introduced by the colliding jets. The atomization of gelled fluids was improved by using a colliding liquid jet, which acts as an atomization assistant which generates disturbances to the gel/liquid film. Unlike jet impingement of gels, even with same jet momentum, creates a shear layer in the collision sheet due to the different jet velocities, improving the atomization process.